1996
DOI: 10.3109/00016349609033355
|View full text |Cite
|
Sign up to set email alerts
|

A placebo‐controlled trial of oral ergometrine to reduce postpartum hemorrhage

Abstract: Oral ergometrine has too little effect on blood loss after childbirth in order to be a good alternative to parenteral prophylactic management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 16 publications
0
36
0
Order By: Relevance
“…Therefore, without a skilled attendant present to make the injection, ergometrine and oxytocin cannot be chosen for PPH management in home births in developing countries where most deliveries occur. Alternative methods like nipple stimulation and oral ergometrine have shown no advantage over injectable uterotonics [41,42].…”
Section: Postpartum Hemorrhagementioning
confidence: 99%
“…Therefore, without a skilled attendant present to make the injection, ergometrine and oxytocin cannot be chosen for PPH management in home births in developing countries where most deliveries occur. Alternative methods like nipple stimulation and oral ergometrine have shown no advantage over injectable uterotonics [41,42].…”
Section: Postpartum Hemorrhagementioning
confidence: 99%
“…In the trial by Ilancheran 1990, the only information given is that it was the 'standard dose'. The ergot alkaloid arm was even more varied, ranging from slightly different preparations -ergometrine/ergonovine (De Groot 1996;Fugo 1958;Ilancheran 1990;McGinty 1956;Sorbe 1978), methylergonovine maleate (Howard 1964), and methergine (McGinty 1956); different doses -from 0.2 mg (Howard 1964;McGinty 1956;Sorbe 1978), to 0.4 mg (De Groot 1996), 4 mg (Fugo 1958), and the 'standard dose' in Ilancheran 1990; and different routes -all intravenous except oral in De Groot 1996. In one trial, the oxytocin was given after placental delivery (Howard 1964), and in one trial, the study was carried out within the context of expectant management of the third stage of labour (De Groot 1996).…”
Section: Comparison B: Oxytocin Versus Ergot Alkaloidsmentioning
confidence: 99%
“…34-40.64). No significant difference was observed in the use of additional uterotonics in two trials in the systematic review (24,25): in 35 of 557 women given oxytocin and 46 of 651 women given ergometrine (RR 1.02, 95% CI 0.67-1.55).…”
Section: Oxytocin Vs Ergometrinementioning
confidence: 90%
“…One trial (24) included in the systematic review reported on the critical outcomes of blood loss of >1000 ml and need for blood transfusion. There was no difference in incidence of blood loss >1000 ml (RR 1.09, 95%CI 0.45-2.66).…”
Section: Oxytocin Vs Ergometrinementioning
confidence: 99%